Conceptualising and Understanding Artistic Creativity in the Dementias: Interdisciplinary Approaches to Research and Practise - Camic, Paul M.; Crutch, Sebastian J.; Murphy, Charlie; Firth, Nicholas C.; Harding, Emma; Harrison, Charles R.; Howard, Susannah; Strohmaier, Sarah; Van Leewen, Janneke; West, Julian; Windle, Gill; Wray, Selina; et al. (Frontiers in Psychology, 2018)
Creativity research has a substantial history in psychology and related disciplines; one component of this research tradition has specifically examined artistic creativity. Creativity theories have tended to concentrate, however, on creativity as an individual phenomenon that results in a novel production, and on cognitive aspects of creativity, often limiting its applicability to people with cognitive impairments, including those with a dementia. Despite growing indications that creativity is important for the wellbeing of people living with dementias, it is less well understood how creativity might be conceptualised, measured and recognised in this population, and how this understanding could influence research and practice. This paper begins by exploring prevailing definitions of creativity and co-creativity and assesses their relevance to dementia, followed by a critique of creativity and dementia research related to the arts. Perspectives from researchers, artists and those with a dementia are addressed. We then introduce several novel psychological and physiological approaches to better understand artistic-related creativity in this population and conclude with a conceptualisation of artistic creativity in the dementias to help guide future research and practice.